Effect of UV-C treatment on sanitised and unsanitised ready-to-eat leafy green vegetables, produced in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Albany Campus, New Zealand - Abthiyar, Lovina (Massey University, 2023)
Several outbreaks in ready-to-eat (RTE) salads have been reported with major concerns comprising of enteric pathogens such as Coliforms, Listeria (L.) monocytogenes and Salmonella spp. that have fast growth rates and low infectious doses. To improve the microbial safety of RTE salads, various methods have been used including non-thermal ultraviolet (UV) irradiation. Non-thermal UV irradiation causes fewer changes in the nutrition and sensory quality of food, compared to the conventional methods. This study investigated the effect of non-thermal UV-C dosage on microbiological levels of fresh commercial samples of sanitised (n=4) and unsanitised (n=4) spinach, kale, rocket and mesclun using 100 mJ/cm² dosage including controls. A commercial company in New Zealand supplied eight (n=8) freshly prepared commercial and packaged RTE salad samples. The sanitised samples had undergone normal preparation steps which included cutting, washing, and sanitation. The packaged samples (n = 8) were transported under chilled conditions (4°C) to Massey University Auckland Campus. Upon delivery, the samples were coded and treated by irradiation at 100 mJ/cm² (Radiant UV-21A0043, International Light Technologies, Inc. USA). The control and test (treated) samples were re-packaged in heat-sealed micro-perforated bags and stored for 12 days/4°C. Sample packages were retrieved on days 0, 4, 8 and 12 for analysis of total aerobic mesophilic counts (AMC), Coliforms, L. monocytogenes, S. aureus and Salmonella spp. using standard methods. The weight and colour (Minolta, Japan) of the samples were measured as well as evaluated by a focus sensory group for colour, texture, flavour, juiciness, firmness and aroma. UV-C treatment (100 mJ/cm²) successfully reduced total AMC in all the sanitised and unsanitised salad samples (n=8) and no pathogens were detected during storage for 12 days/4°C. During storage, the AMC increased (p0.05) on the AMC. Kale samples recorded lower AMC for the irradiated samples (p<0.05). UV-C treatment of salads increased the lightness L* for all the samples except for rocket, decreased the yellowness b* for spinach and kale samples and did not affect the greenness a* of the salads. The lightness L* was lower (p0.05) on the greenness a* of spinach, kale, mesclun and rocket samples. The yellowness b* of spinach and kale was significantly affected by the dosage and the storage period (p0.05) on the b* value. Sanitization had a significant effect on the rocket samples (p<0.05) as sanitised rocket had a lower b* value than the unsanitised rocket. The effect of UV-C treatment on the weight loss (%) of salad samples was different for each salad. The weight loss (%) was higher in UV-treated spinach and kale samples than in the respective controls. Mesclun samples had the highest weight loss for control samples than UV-treated samples. For rocket salads, unsanitised controls (non-UV-treated) had higher weight loss than the unsanitised treated sample and the sanitised treated sample had slightly higher weight loss than the sanitised control sample. Focus group sensory evaluation indicated that UV-treated salads had better taste than control samples, although the appearance, texture and colour were poorer than the non-UV-treated samples. Overall, UV treatment reduced AMC in RTE salads without affecting the taste of the vegetables for 12 days/4°C. However, more work is required to maintain the overall appearance and texture of UV-treated salads.
Figure 2.5 (=Delorme et al., 2020, Fig 4) was removed for copyright reasons.
Keywords: 300604 Food packaging, preservation and processing